Facial Papules and Renal Carcinoma: A Quiz - Niccolò Capurro; Silva Riva; Mattia Fabio Molle; Emanuele Cozzani; Antonio Guadagno; Aurora Parodi (Medical Journals Sweden, 2022)
Abstract is missing (Quiz)